Teachers and Teacher Education: Limitations and Possibilities of Attaining SDG 4 in South Africa - Toyer Nakidien; Marcina Singh; Yusuf Sayed (MDPI AG, 2021)
As we enter the last ten years leading to the realisation of the Sustainable Development Goals in 2030, African countries are still plagued with poverty and underdevelopment. For most children in Africa, the attainment of Sustainable Development Goal (SDG) 4 will remain elusive. Drawing from two interrelated empirical studies, one focusing on citizenship and social cohesion at high school level and the other on the implementation of assessment for learning at primary school level, it was found that not only are schools not equipped to provide the quality education as set out in SDG 4, but teachers need additional training to give expression to the ideals of SDG 4. In order for this to be adequately addressed, all interested stakeholders-government, business, and NGOs-need to be involved.